Prevalence of ectoparasites on Lates calcarifer (Seabass fish) from cage aquaculture population of Kampung Trayong and Tanjung Badak, Kuala Mengkabong, Tuaran district, Sabah / Kasra Mukti - Mukti, Kasra (2016)
A study of prevalence of ectoparasites on Lates calcarifer (seabass fish) from cage aquaculture was conducted at Ko-Nelayan, Kampung Trayong and Perikanan, Tanjung Badak, Kuala Mengkabong, Tuaran District, Sabah. The aims of this study were to examine and identify the common ectoparasites that have infected the Lates calcarifer (seabass fish) in cage aquaculture. Further, to evaluate the prevalence and intensity of ectoparasites on seabass fish for cage aquaculture at two stations cage Aquaculture Center at Kampung Trayong and Tanjung Badak, Kuala Mengkabong, Tuaran district, Sabah. Finally, to determine the abundance of ectoparasites at different infected body part from 60 samples of fish those were randomly taken from cage. The sample of ectoparasites was done by scrapping the mucous on three different parts of body including lateral body, caudal fin and dorsal fin. Then, the specimen was observed under compound microscope for ectoparasites identification. The data analysis used such as prevalence and intensity calculation. In this study the common ectoparasites were found to had infected the seabass fish in cage aquaculture at Tuaran district such as under the group of Acanthocephala, Branchiura (Fish Lice), Copepods, Didymozoidea, Digenea (Flukes), Nematoda (Roundworms), Monogenea, and Protozoans. The highest prevalence and intensity of ectoparasites on seabass fish was found at dorsal fin which is 66.67 % and 1.95 respectively. Finally, the most abundance ectoparasites that can be found at three different infected body parts that is Eustrongylides sp. While, the less abundance of ectoparasites that can be found at dorsal and caudal fin that is Iheringascaris inquires, whereas at lateral body, the less abundance of ectoparasites such as Rhadinorhynchus pristis, Caligus sp., Lepeophtheirus bermudensis, Contracaecum spiculigerum and Syncleithrum sp.